Acupuncture for Post-Stroke Cognitive Impairment: An Overview of Systematic Reviews - Li L; Yang L; Luo B; Deng L; Zhong Y; Gan D; Wu X; Feng P; Zhu F (International Journal of General Medicine, 2022)
Liuying Li,1 Lanying Yang,2 Biao Luo,2 Lvyu Deng,2 Yue Zhong,2 Daohui Gan,2 Xiaohan Wu,2 Peimin Feng,1 Fengya Zhu2 1Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu, People’s Republic of China; 2Traditional Chinese Medicine Department, Zigong First People’s Hospital, Zigong, People’s Republic of ChinaCorrespondence: Peimin Feng; Fengya Zhu, Email fpmmed@cdutcm.edu.cn; notfounds@foxmail.comBackground: Post-stroke cognitive impairment (PSCI) is one of the most common complications after stroke. In recent years, as a complementary alternative therapy, many systematic reviews (SRs) and meta-analysis (MAs) have reported the efficacy and safety of acupuncture in improving cognitive function in patients with PSCI, but the quality of evidence is unknown and therefore needs to be evaluated comprehensively.Aim: We aimed to evaluate the SRs of acupuncture for patients with PSCI, to summarize the evidence quality of SRs to provide scientific evidence.Methods: We searched for relevant SRs and MAs in seven databases up to March 22, 2022. Two reviewers independently completed literature retrieval, screening, and data extraction. We used A Measurement Tool to Assess Systematic Reviews 2 (AMSTAR 2) to evaluate the methodological quality; the Grading of Recommendations Assessment, Development and Evaluation (GRADE) tool to determine the strength of evidence; and the ROBIS tool to assess RoB.Results: We identified 14 SRs. The methodological quality of all SRs was low (2/14) or very low (12/14). GRADE results showed 13 were moderate quality (26%), 5 were low quality (10%), and 32 were very-low quality (64%). RoB showed that one SR had a low risk and 13 had a high risk. Moderate quality results showed that combined acupuncture therapy was superior to western medicine or cognitive rehabilitation training in improving cognitive function, the total response rate, and the daily living ability of patients with PSCI.Conclusion: Based on the evidence, acupuncture appears to be effective and safe in improving cognitive function for patients with PSCI, but the overall quality of SRs is not high. High-quality randomized controlled trials are needed to confirm the effectiveness and safety of acupuncture on the cognitive function of patients with PSCI.Systematic Review Registration: PROSPERO CRD42022315441.Keywords: acupuncture, PSCI, overview, AMSTAR-2, GRADE